Análise dos impactos ambientais decorrentes da implantação da Avenida Contorno Leste, no entorno dos bairros São João Del Rei e Osmar Cabral, Cuiabá-MT - Teixeira, Gilvani Leandro Sales (2024)
This dissertation analyzes the degraded environmental situation of a portion of Avenida Contorno Leste, located in Cuiabá/MT, near the neighborhoods of São João Del Rei, Osmar Cabral and the residents of Bom Jesus and Brasil 21. To carry out this theoretical essay and construct this framework, the principles and concepts guided by the book Environmental Impact Assessment by Luis Enrique Sánchez (2013) were followed, together with the writings of leading authors in the area of Environmental Impact Studies and Environmental Impact Reports (EIA/RIMA). Among the environmental impacts highlighted, the removal of vegetation cover and riparian forests, followed by soil waterproofing, implementation of a diversion system and channeling of intermittent and continuous water flows (tributaries) connecting to the Coxipó River, and the end of the construction of the bridge over the Coxipó River, stand out. In short, the environmental impact matrix is a practical tool that condenses and simplifies environmental impacts, with the organizational objective of facilitating the reader's understanding and the process of analysis and discussion of it.